Following the Crowd: Leisure Complementarities Beyond the Household - Simon Georges-Kot; Dominique Goux; Eric Maurin (Institute for the Study of Labor (IZA), 2014)
Leisure externalities across households have potentially very important implications for labor market regulations, but they have proven difficult to identify. This paper exploits the unique features of school holidays and regulations about paid leave in France to identify how changes in the timing of work and leisure activities for individuals living with children affect the time use decisions of individuals living in other households. We find that exogenous increases in holidays for individuals living with children actually induce very significant increases in the demand for holidays from individuals living in other households. These positive interactions across households are all the more striking as exogenous increases in the number of individuals on holidays are also shown to be associated with very significant increases in the costs of holidays.
Keywords: J22; D62; 330; social interactions; leisure demand; paid leave; school holidays